Puerarin Relieved Compression-Induced Apoptosis and Mitochondrial Dysfunction in Human Nucleus Pulposus Mesenchymal Stem Cells via the PI3K/Akt Pathway - Donghua Huang; Yizhong Peng; Kaige Ma; Xiangcheng Qing; Xiangyu Deng; Zhiliang Li; Zengwu Shao (Stem Cells International)
Puerarin (PUR), an 8-C-glucoside of daidzein extracted from Pueraria plants, is closely related to autophagy, reduced reactive oxygen species (ROS) production, and anti-inflammatory effects, but its effects on human nucleus pulposus mesenchymal stem cells (NPMSCs) have not yet been identified. In this study, NPMSCs were cultured in a compression apparatus to simulate the microenvironment of the intervertebral disc under controlled pressure (1.0 MPa), and we found that cell viability was decreased and apoptosis level was gradually increased as compression duration was prolonged. After PUR administration, apoptosis level evaluated by flow cytometry and caspase-3 activity was remitted, and protein levels of Bas as well as cleaved caspase-3 were decreased, while elevated Bcl-2 level was identified. Moreover, ATP production detection, ROS, and JC-1 fluorography as well as quantitative analysis suggested that PUR could attenuate intercellular ROS accumulation and mitochondrial dysfunction. Besides, the rat tail compression model was utilized, which indicated that PUR could restore impaired nucleus pulposus degeneration induced by compression. The PI3K/Akt pathway was identified to be deactivated after compression stimulation by western blot, and PUR could rescue the phosphorylation of Akt, thus reactivating the pathway. The effects of PUR, such as antiapoptosis, cell viability restoration, antioxidation, and mitochondrial maintenance, were all counteracted by application of the PI3K/Akt pathway inhibitor (LY294002). Summarily, PUR could alleviate compression-induced apoptosis and cell death of human NPMSCs in vitro as well as on the rat compression model and maintain intracellular homeostasis by stabilizing mitochondrial membrane potential and attenuating ROS accumulation through activating the PI3K/Akt pathway.